Risk of post-traumatic stress disorder in women after miscarriage - Białek, Katarzyna; Malmur, Mariusz (Medical Studies/Studia Medyczne, 2020)
Loss of pregnancy as a result of miscarriage may cause many undesirable psychological reactions, including the risk of posttraumatic stress disorder. Its consequences are often an important clinical problem, which entails a variety of complications that may affect the overall functioning of women and their partners. Understanding the type and frequency of emotional responses to pregnancy loss is therefore essential to target appropriate support, thus minimising mental illness and health costs in long-term care. Supporting women after a miscarriage can also help build a constructive relationship with the children born after the loss, so that unresolved grief and depression do not affect their formation in a negative way. Proper communication and reliable and empathetic feedback from health professionals also seem important. The aim of the article is to describe the psychological reactions of women after miscarriage and to assess the factors that affect their occurrence.